2021
DOI: 10.1155/2021/2406646
|View full text |Cite
|
Sign up to set email alerts
|

Topical Vitamin C Promotes the Recovery of Corneal Alkali Burns in Mice

Abstract: Background. Vitamin C (Vc) has been found to promote corneal wound healing after alkali burns. However, the specific mechanism and functional modes are still unclear. The present study sought to assess the mechanisms of Vc function on corneal alkali burns. Methods. Eighty BALB/c mice were divided into four groups: a normal group without alkali injury (n = 10), an alkali injury group without any treatment (1-day group, n = 10), a Vc group treated with topical 10% Vc (Vc group, n = 30), and a control group treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In a similar vein, experiments using a mouse model have revealed that the application of topical vitamin C can ameliorate the infiltration of inflammatory cells within the cornea, foster the proliferation of limbal stem cells, and curtail the formation of new blood vessels in the cornea following alkali burns. 62,63 Vitamin E belongs to a group of fat-soluble compounds distinguished by a chromanol ring with a side chain at the C2 position. It is renowned for its antioxidative properties, which play a role in bolstering the eye's antioxidant defenses, potentially aiding in the prevention of DED.…”
Section: Vitamins C and E In Relation To Dedmentioning
confidence: 99%
“…In a similar vein, experiments using a mouse model have revealed that the application of topical vitamin C can ameliorate the infiltration of inflammatory cells within the cornea, foster the proliferation of limbal stem cells, and curtail the formation of new blood vessels in the cornea following alkali burns. 62,63 Vitamin E belongs to a group of fat-soluble compounds distinguished by a chromanol ring with a side chain at the C2 position. It is renowned for its antioxidative properties, which play a role in bolstering the eye's antioxidant defenses, potentially aiding in the prevention of DED.…”
Section: Vitamins C and E In Relation To Dedmentioning
confidence: 99%